PERANAN MUHAMMAD SANI DALAM PEMBANGUNAN INFRASTRUKTUR DI KABUPATEN KARIMUN TAHUN 2001-2005 - Marzanizam Marzanizam; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Muhammad Sani was a figure of infrastructure development in Karimun District in 2001-2005 when he served as the first definitive Regent in Karimun Regency. The purpose of this study was to find out the life history of Muhammad Sani, to find out what infrastructure development was built by Muhammad Sani in Karimun Regency, to find out the obstacles and challenges of Muhammad Sani in the construction of infrastructure in Karimun District, to find out the community's response to infrastructure development carried out Muhammad Sani in Karimun District. The method used in this research is qualitative method. Data obtained from the results of interviews were then analyzed in their own language. The research location is Karimun Regency, Riau Islands Province. This research began to be carried out since the beginning of this research title was submitted until this thesis was finished. Data collection techniques used are documentation techniques, library study techniques, interview techniques. The results of the study show that Muhammad Sani has a role in advancing development in the field of infrastructure in Karimun Regency. Muhammad Sani has done a lot of infrastructure development in the field of government building infrastructure, health infrastructure, education infrastructure, transportation infrastructure, religious infrastructure, and sports infrastructure. The development that Muhammad Sani had done gave a lot of benefits to Karimun Regency which was a district that had just been expanded at that time. Keywords: Muhammad Sani, Infrastructure Development, Karimun Regency